Weak Solutions to a Landau–Lifshitz Equation with a p-Laplacian Operator as an Exchange Field. (17th September 2022) - Men, Xiuping; Ayouch, Chahid; Tilioua, M.; Sidi Ammi, M. R.; Zeb, Anwar; Sehra; Djilali, Salih
Abstract : We are dealing with the classical Landau–Lifshitz equation with an unusual exchange field expressed in terms of a p -Laplacian operator for p greater than 2. We obtain weak solutions to the model by using penalization, compactness arguments, and monotonicity method.